Role of Attitude as a Mediator in the Relationship between Entrepreneurial Education and Intention to Become an Online Entrepreneur among Online Distance Learning Students in Malaysia - Zahir Osman; Ratna Khuzaimah Mohamad; Zulhairi Zakariah; Liana Mohamad (ASEAN Journal of Open and Distance Learning, 2019)
This study focuses on evaluating the indirect relationship among entrepreneurial education, attitude and intention to become an online entrepreneur among students in Online Distance Learning higher institutions in Malaysia. To assess the indirect effect of attitude on the relationship between entrepreneurial education and intention, the Structural Equation Model technique was employed. The model was designed and later analysed using the Partial Least Square procedure on data collected from a survey that yielded 317 usable questionnaires. The results demonstrated that attitude has a mediating effect on the relationship between entrepreneurial education and intention to become an online entrepreneur among students in Malaysian Online Distance Learning higher institutions. The findings suggest that Online Distance Learning institutions should give a greater emphasis on strengthening entrepreneurial education and attitude to ensure their Online Distance Learning students have strong intention to become online entrepreneurs. (Abstract by authors)